Avaliação do desenho da política pública de migrações, refúgio e apatridia - Nogueira, Tiago Amorim (2021)
Migrations have always been present in human history, and especially in the modern era, huge contingents of men, women, children and elderly people move across the planet in different situations and contexts, both spontaneously and forcibly. In this sense, based on the analysis of the situation of refugees in the Brazilian neoliberal context, this study aimed to evaluate the design of the Public Policy on Migration, Refuge and Statelessness in Brazil with a view to understanding the mechanisms for implementing and enforcing this policy and contributing to its improvement as a social policy. Therefore, it was necessary to develop a theoretical- methodological study on the referential bases of the Policy under discussion, provided for in Article 120 of Law 13,445/2017 (BRASIL, 2017) and the collection of institutional and normative documents with the bodies responsible for the implementation policy (Federal Executive Branch, Ministry of Justice - through CONARE) and by a Civil Society Organization of the municipality of São Paulo (SP). In the methodological path, I carried out bibliographical and exploratory research, of an eminently qualitative nature, but without giving up quantitative data issued by international organizations (such as the United Nations High Commission for Refugees – UNHCR). In order to analyze the data and documents collected, I sought to carry out a detailed description of the actions taken by the various actors involved with this theme at the national level, promoting an articulation that permeated the dimensions of In-Depth Assessment (RODRIGUES, 2008). At the end, I presented the design of the evaluation of the Policy on Migration, Refuge and Statelessness in a hermeneutic paradigm, in line with the perspective of Lejano (2012).